Men and Women Language Features and Styles Used in “The End of the F***ing World”, A Netfilx TV Series - Karima Zansabil (Universitas PGRI Adi Buana Surabaya, 2023)
The occurrence of different language features and language styles used by its speakers during a conversation is believed to be affected by some factors, such as gender (Coates, 2015; Lakoff, 1973; Tannen, 1990), situation, and the topic discussed in the conversation (Fishman, 2003). The scripts from a TV Series entitled The End of the F***ing World were analyzed to find out whether the characters way in choosing the language to be used is based on those factors. The result showed that the way the characters used the language is different according to the situation they been through. Furthermore, the result suggested that gender does not always influence the language used by its speakers.